The relationship and effects of social media usage and social comparison on self-esteem - Guðjón Hlynur Sigurðarson 1999- (2022)
Abstract People seeks to surround themselves with others because they´re social beings. The 21st century has offered people to join a new and an exciting social environment called social media. Social media has just about 4 billion active users where it provides information and allows people to communicate in various ways. Being exposed to social media platforms, such as Facebook and Instagram, has led people to spend at least two and a half hours on daily basis using it. Excessive use of social media has led people to have lower self-esteem while at the same time to show higher social comparison. The purpose of the current study was to see whether people with high social comparison that spent a lot of time using Facebook or Instagram, had lower self-esteem. The sample of the study were people who lived in Iceland, 18 years old or older (N =234). Results showed that interaction effects of high social comparison and more social media usage did not have any significant effect on people´s self-esteem. Other hypotheses were tested which showed significant results. Keywords: social beings, social media, social media usage, Facebook, Instagram, well-being, social comparison, self-esteem Útdráttur Fólk sækist í það að umkringja sig öðrum vegna þessa að mannfólkið eru félagsverur. Tuttugasta og fyrsta öldin hefur gert fólki kleift á að sameinast í nýtt félagslegt umhverfi sem kallast samfélagsmiðlar. Það eru um 4 milljónir virkra notenda á samfélagsmiðlum en þeir eru ákveðin upplýsingaveita og einnig samskiptamiðill. Fólk er farið að verja tíma sínum mikið í samfélagsmiðla hver notandi ver um það bil tveimur og hálfri klukkustund á hverjum degi í að skoða miðlana. Óhófleg notkun hefur leitt til þess að fólk hefur minna sjálfsálit, á sama tíma og þá ber það sig meira saman við aðra. Rannsókn þessi vildi skoða hvort fólk sem ber sig mikið saman við aðra og á sama tíma notar mikið samfélagsmiðla, sé með lægra sjálfsálit. Úrtakið var fólk sem býr á Íslandi sem er 18 ára eða eldra. Niðurstöður sýndu að samvirknihrif ...